Tissue nanotransfection and cellular reprogramming in regenerative medicine and antimicrobial dynamics - Shakra, Mohammed Youssef (Frontiers in Bioengineering and Biotechnology, 2025)
Tissue nanotransfection (TNT) is a novel, non-viral nanotechnology platform that enables in vivo gene delivery and direct cellular reprogramming through localized nanoelectroporation. This review synthesizes current advancements in TNT, outlining its device architecture, electroporation principles, and optimized delivery of genetic cargo, including plasmid DNA, mRNA, and CRISPR/Cas9 components. The mechanisms underlying TNT-mediated cellular reprogramming are critically evaluated, including transcriptional activation, epigenetic remodeling, and metabolic shifts, across three major reprogramming strategies—induced pluripotency, direct lineage conversion, and partial cellular rejuvenation. TNT demonstrates transformative therapeutic potential in diverse biomedical applications, including tissue regeneration, ischemia repair, wound healing, immunotherapy, and antimicrobial therapy. This review highlights TNT’s unique advantages over traditional gene delivery systems, namely, its high specificity, non-integrative approach, and minimal cytotoxicity, while also addressing existing limitations such as phenotypic stability and scalability. By integrating emerging data and identifying key translation challenges, this work positions TNT as a conceptual and technological advance in regenerative medicine and targeted gene therapy, offering a roadmap for future research and clinical implementation.